Enantioselective phase-transfer catalyzed alkylation of 1-methyl-7-methoxy-2-tetralone: an effective route to dezocine - Li, Ruipeng; Liu, Zhenren; Chen, Liang; Pan, Jing; Zhou, Weicheng (Beilstein Journal of Organic Chemistry, 2018)
In order to prepare asymmetrically (R)-(+)-1-(5-bromopentyl)-1-methyl-7-methoxy-2-tetralone (3a), a key intermediate of dezocine, 17 cinchona alkaloid-derived catalysts were prepared and screened for the enantioselective alkylation of 1-methyl-7-methoxy-2-tetralone with 1,5-dibromopentane, and the best catalyst (C7) was identified. In addition, optimizations of the alkylation were carried out so that the process became practical and effective.
Keywords: alkylation; asymmetric catalysis; cinchonidine; dezocine